DIFFERENT BIOLOGICALLY ACTIVATED SYSTEMS RESISTANCE TO INHIBITION (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2005)
Biologically activated sorbent (BAS) are believed to be more efficient than separate conventional activated sludge and sorbents systems in removing phenols and others persistant organic pollutants from wastewater. These days, applications of biological activated systems treatment for various kinds of industrial wastewater are attracting greater attention as one of the efficient technologies. But the process is not very good understood, and there is not much parameter, which could describe stability and reliability of system and which could compare different BAS systems. The aim of this study was to investigate the resistance of different biologically activated sorbents to inhibition using respirometric measurements. To choose the most resistant to inhibition biologically activated system from five BAS: BAS-A, BAS-B, BAS-C, BAS-D and conventional activated sludge for comparing. Also to evaluate potential applicability of respirometric method for monitoring bioactivity in BAS systems. The pesticide 3,5-dichlorenol was chosen as inhibitor compound for experiment. The respiratory inhibition measurements were done with different biologically activated systems using different concentration of pesticide. The experiment was accomplished using respiratory inhibition method which described in Lithuanian normative document for environmental protection (Land 45-2001): activated sludge respiratory inhibition test. In parallel saprophyte bacterial counts were determined by spread plate technique and calculated as amount of saprophyte in one litter. The results from both tests showed that the most resistance system to respiratory inhibition was BAS-A. Respirometric method is applicable for monitoring bioactivity in BAS systems.